Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan - Hiruta, Shimpei F.; Kakui, Keiichi (Zootaxa, 2016)
We describe three new species of brackish-water ostracods representing two genera in the ostracod tribe Thalassocypridini from mangrove forests in the Ryukyu Islands, subtropical southwestern Japan, and provide their barcoding sequences for the mitochondrial cytochrome c oxidase subunit I (COI) gene. Mangalocypria ryukyuensis sp. nov. was found on Okinawa Island. We also found a Mangalocypria population on Ishigaki Island that was morphologically identical to M. ryukyuensis on Okinawa, but an individual differed by 4.7% in COI sequence (K2P distance) from an individual from Okinawa. This is the first record for Japan of a species in Mangalocypria. Paracypria longiseta sp. nov., obtained from Okinawa Island, is similar to Pontoparta hartmanni. Paracypria plumosa sp. nov. from Ishigaki Island is similar to Pa. adnata described from Yakushima Island, Japan. The COI genetic distance between individuals of Pa. longiseta and Pa. plumosa was roughly as large as that between either of these species and individuals in the Mangalocypria populations. Our study underscores that genera in Thalassocypridini may not represent natural groups, and that this tribe needs taxonomic revision.